Factors Causing Lack of Students' Learning Motivation in the Online Learning Process During the COVID-19 Pandemic Class X at SMK Negeri 4 Sinjai - Nasrullah, Muh.; Wahdaniar, Nur; Saleh, Sirajuddin; Nurjannah, Nurjannah (Universitas Negeri Makassar, 2022)
Education is one of the efforts made by individuals to save the survival of culture, civilization and build personality according to existing norms, as well as education as an effort to realize an effective learning process to foster students. Motivation is a conscious action in the form of energy within a person or individual that encourages him to carry out activities in order to achieve the goals to be achieved. In simple terms, motivation can be interpreted as the basic impulse that moves someone to do something. Students who have high motivation in learning have a great urge to carry out learning activities or give a positive response to the learning activities that are followed. On the other hand, students who have low motivation will not take learning activities seriously. This study was carried out with the aim of knowing the factors causing the lack of learning motivation of students in the online learning process during the COVID-19 pandemic class X at SMK Negeri 4 Sinjai. This study uses a quantitative research approach with a descriptive type of research. The population in this study were students of class X SMK Negeri 4 Sinjai, with a population of 47 people. Data was collected using various techniques including observation, questionnaires, interviews and also documentation. The data analysis technique used is factor data analysis. The results showed that the factors causing the lack of learning motivation of students during the online learning process during the Covid-19 pandemic were two factors, namely internal and external factors, which were included in internal factors including interest and concentration, intelligence, extracurricular, talent, attitude. which are included in external factors including the family environment, school environment